Destino social de alguns egressos do curso de pedagogia de uma instituição de ensino superior privada com baixa avaliação no Ministério da Educação - Pita, Tatiana de Jesus (2011)
This present study is the result of a preliminary research conducted in 2010. It aims to characterize, according to the socioeconomic and cultural origin, the graduated students of the Course in Pedagogy from a private Higher Education Institute which achieved low ranking in ENADE and also in the Institutional Evaluation of MEC. This institute is located in a city nearby São Paulo. It aims to identify where these students coming from this institute work as well. It also examines, through the offered wage weather there is a relation between the professional performance, their training and the prestige of the institute. The hypothesis was defined as: teacher education graduates from private institute with low classification is incomplete, due to the curriculum structured to speed up the course of Pedagogy, so the professional performance of these people becomes uncertain. For this purpose, we investigated the graduated students in Pedagogy from a private Higher Education Institute located in a city near São Paulo . As a methodological procedure, questionnaires were applied with semi structured questions to the graduated students in Pedagogy, graduated between 2007 and 2010. In the data analyses it was used concepts of capital cultural, social, economic and educational advocated by Pierre Bourdieu. It was found that the diploma gotten in the Pedagogy course of Higher Education Institute with low ranking, coming from popular classes failed to secure a social or economic rise in relation to the other social classes . But among its members (spouse, family), the cultural capital and the school history of these people has been expanded, creating a symbolic value to the diploma